β-CAROTENE INFLUENCE ON IMMUNE STATUS OF CHILDREN AFTER THYMECTOMY - A.L. Frolenko; A.I. Smolyagin ("Paediatrician" Publishers LLC, 2011)
Surgical treatment of congenital heart disease is quite often accompanied by total or partial resection of thymus, due to heart access.  Thymectomycan lead to various immunological abnormalities. 43 children aged 3 to 6 years, operated due to congenital heart disease with partial or total thymectomy, took part in the research. Immunological status was measured using tests of 1 and 2 levels after 1 and 2 years from the surgery. β-carotene treatment had positively influenced on changes in immunological status of children that underwent thymectomy, and that proposes immunomodulating activity of the medication under consideration and its use as a nonspecific immunomodulator in children. Key words: children, thymectomy, β-carotene, congenital malformations. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 98-101.)